Bohemisms in Old Ukrainian literature monument «Lucidarius» - Aleksiayevich, Hanna V. (Journal of the Belarusian State University. Philology, 2023)
The article is devoted to Old Ukrainian literature monument «Lucidarius», which came down to us in several copies. This monument is a translation of Old Czech apocryphal work «Lucidář». The focus of the study is the language of three Old Ukrainian copies, which contains numerous borrowings of foreign Slavonic origin – Czech, Polish and Church Slavic. The presence of Polonisms and Church Slavicisms is explained by the general conditions of the development of the Old Ukrainian written language, which was under the lasting influence of the Polish and Church Slavic languages. Czech loanwords, or Bohemisms, penetrated into Old Ukrainian literature monument «Lucidarius» directly from the source of translation. The results of the historical and etymological analysis revealed the following Bohemisms: гнед, звѣрница (звѣраница), кузло (каузлостосъ), кожула, лепкое (липское) море. A detailed study of the West Slavic (in particular, Czech) language influence on the literature monuments of East Slavic writing scribes contributes to a better understanding of processes of inter-Slavic interaction.